Shooting performance in archery: a perspective of dynamic-static balance - Kesilmis, I.; Sögüt, F.; Çömelekoglu, Ü. (Sport Sciences for Health, 2024)
Background It is of great importance for archers to have a stable posture for successful shooting. In studies conducted on this subject, attention is drawn to the necessity of postural stability in archers for a successful shooting performance. Balanced posture, which is an important parameter, includes the preservation of the center of mass on the support base. In this study, it is aimed to examine the correlation between dynamic and static balance and achievement score in archers.